Small implants nella protesica di spalla - Stoppani, C.; Randelli, P.S. (Lo Scalpello - Journal, 2019)
SMALL IMPLANTS IN SHOULDER ARTHROPLASTY In over a century of history, shoulder prosthetics has seen numerous developments in terms of both design and surgical indications: from the first monobloc hemiarthroplasty proposed by Neer, many innovations have occurred, which led to the development of complete modular prostheses. Nowadays, anatomic shoulder arthroplasties are able to adapt to patient-specific anatomical characteristics. Reverse shoulder arthroplasty, which revolutionised articular biomechanics, has provided a possible solution for the treatment of patients with rotator cuff failure. The attempt to reduce complications related to traditional implants and the desire to guarantee greater bone stock preservation have pushed the research towards a progressive reduction in humeral stem length until its complete elimination. At the same time, researchers have studied and developed surface implants that reduce pain with minimal changes in the original anatomy. Humeral head resurfacing consists in a metal cap that covers the articular portion of the proximal humeral epiphysis without any substantial osteotomy of the humeral head. Despite their recent introduction, the results offered by the so-called small implants appear to be very promising and it is reasonable to expect their significant diffusion in the future.